An analysis of Personal Protective Equipment (PPE) costs incurred by the contractors of MRT Projects / Izatul Farrita Mohd Kamar ... [et al.] - Mohd Kamar, Izatul Farrita; Umari, Mohd Hadi Putra; Lop, Nor Suzila; Che Ahmad, Asmalia (2021)
The construction of rail infrastructure projects such as Mass Rapid Transit (MRT) is expanding in Malaysia to enhance and integrate the urban public transportation services. However, fatalities, serious injuries, and damage to properties occur every year due to the rapid construction of this project. The costs of these injuries to an organisation are very crucial in establishing how much it should spend on safety control. Most of the contractors had some problems with the safety budget. The budget is always overrun due to the lack of systematic calculation during the construction stage. Thus, the safety budget required is not clearly defined and specified in the existing contract document. Most of them are not able to identify the safety items clearly and do not know the requirements required for the project, causing them to estimate the safety budget by using their experience. The effect causes the defective budget system for the construction project. This research aims to analyse the Personal Protective Equipment (PPE) costs that are most incurred by the contractor of MRT projects. A quantitative method was used in this research. The questionnaires were distributed to the Work Packages Contractor (WPC) who were involved for guideway (viaduct) package works in MRT projects. The finding shows that the types of PPE like steel toe safety shoes, traffic vest and earplugs (>85 dBA) are the most cost incurred in MRT projects. These findings could assist the contractor to allow a reliable safety budget during the pre-contract stages.